Lima, and the Classic Approach to Urban Mobility as an Exclusion Factor - Conto Quispe, Zulema (2020)
Although for decades the widespread use of the automobile as a means of transport in cities has been questioned, and today many cities focus on calming traffic with policies restricting the use of the car, and / or betting on more displacement modes. sustainable, which corresponds to the offer of spaces adapted to all modes of movement (motorized and non-motorized), in a clear correspondence with the movement patterns of its citizens. However, in the city of Lima it is still committed to motorized and private driving modes, despite the fact that the majority of its population travels by public transport. From this article it is intended to show how this "classic approach to urban mobility" is constituted as a factor of exclusion of the mobility system for various groups.